2006
DOI: 10.1159/000096912
|View full text |Cite
|
Sign up to set email alerts
|

ECCA Grading Scale: An Original Validated Acne Scar Grading Scale for Clinical Practice in Dermatology

Abstract: Introduction: The ECCA grading scale (échelle d’évaluation clinique des cicatrices d’acné) is a tool designed to help dermatologists to assess the severity of acne scars and to standardize the discussions about the treatments of scars. Methods: We developed an acne scar clinical grading scale called ECCA, which consists of 6 items designed to assess easily and quickly the severity of acne scars by a global score. The interobserver reliability of the ECCA grading was statistically validated. Results: The statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(127 citation statements)
references
References 20 publications
2
117
0
3
Order By: Relevance
“…ECCA grading scales are based on semiquantitative, weighted assessments of 6 types of acne scars, namely, V-shaped atrophic scars, U-shaped atrophic scars, M-shaped atrophic scars, hypertrophic inflammatory scars, keloid scars, and superficial elastolysis. 31 Standardized digital photographs were obtained prior to laser treatments and subsequent follow-up photographs were taken using identical camera settings (Nikon D70, Tokyo, Japan) and lighting conditions. To elucidate relationships between acne scar subtypes and response to laser treatments, we classified acne scars into 5 subtypes according to shape and depth (ie, superficial or deep rolling, superficial or deep boxcar, and icepick scars).…”
Section: Outcome Assessmentsmentioning
confidence: 99%
“…ECCA grading scales are based on semiquantitative, weighted assessments of 6 types of acne scars, namely, V-shaped atrophic scars, U-shaped atrophic scars, M-shaped atrophic scars, hypertrophic inflammatory scars, keloid scars, and superficial elastolysis. 31 Standardized digital photographs were obtained prior to laser treatments and subsequent follow-up photographs were taken using identical camera settings (Nikon D70, Tokyo, Japan) and lighting conditions. To elucidate relationships between acne scar subtypes and response to laser treatments, we classified acne scars into 5 subtypes according to shape and depth (ie, superficial or deep rolling, superficial or deep boxcar, and icepick scars).…”
Section: Outcome Assessmentsmentioning
confidence: 99%
“…There are numerous guidelines on the appropriate treatment of acne, and several methods for morphological classification of scars have been proposed. 4,5 However, no consensus has been reached with regard to the evaluation and subsequent classification of acne scars. Although Jacob et al 6 have reported on different treatment options based on acne scar morphology, there is currently no standard treatment for scarring.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the disfiguring effect, the higher the weiting factor assigned ( Table 3). The ECCA has also shown a good interinvestigator reliability [16].…”
Section: Scars Evaluationmentioning
confidence: 95%
“…Goodman and Baron proposed a qualitative scale and then presented a quantitative scale [14,15]. Dreno et al introduced the ECCA scale (Echelle d'Evaluation Clinique des Cicatrices d'Acné) [16].…”
Section: Scars Evaluationmentioning
confidence: 99%